A study on polymerase chain reaction-based HLA DQ ? locus in Elazig, Turkey - Tokdemir, M; Dulger, HE; Akin, H; Doymaz, MZ (Lippincott Williams & Wilkins, 2000)
The polymerase chain reaction (PCR) was used for genetic characterization of 45 samples taken from the city of Elazig in Turkey. The polymorphism at the human leukocyte antigen DQ proportional to locus was detected. Allele and genotype frequencies were determined for unrelated individuals at this locus. Laboratory analyses were done by PCR amplification of DNA. Hybridization to allele specific oligonucleotide probes was performed using a reversed dot-blot typing method. The collected genotype and allele frequencies have been tested, and a comparison was made with other population surveys of this locus. Allele frequencies ranged from 3.3% (allele 1.3) to 36.7% (allele 4), with a discrimination power of 0.92, No deviation was seen from Hardy-Weinberg equilibrium in the findings.
Keywords: forensic science; HLA DQ proportional to; genotype frequency; population genetics; genetic typing; PCR